Ethnic Disparities in Coronavirus Disease 2019 after the Implementation of Universal Screening in Hartford, Connecticut - Veronica Maria Pimentel; Frank Ian Jackson; Anthony Dino Ferrante; Reinaldo Figueroa (Thieme Medical Publishers, Inc., 2021)
Abstract Objective The aim of this article was to estimate the prevalence of coronavirus disease 2019 (COVID-19) in Connecticut, examine racial/ethnic disparities, and assess pregnancy outcomes in pregnant women following the implementation of universal screening for the virus. Materials and methods This is a retrospective cohort study of all obstetric patients admitted to our labor and delivery unit during the first 4 weeks of implementation of universal screening of COVID-19. Viral studies were performed in all neonates born to mothers with severe acute respiratory syndrome coronavirus 2. We calculated the prevalence of COVID-19, compared the baseline characteristics and pregnancy outcomes between those who tested positive and negative for the virus, and determined the factors associated with COVID-19. Results A total of 10 (4.6%) of 220 women screened positive for the virus. All were asymptomatic. Week 1 had the highest prevalence of infection, nearing 8%. No neonates were infected. Hispanics were more likely to test positive (odds ratio: 10.23; confidence interval: [2.71-49.1], p = 0.001). Obstetric and neonatal outcomes were similar between the groups (p > 0.05). Conclusion Although the rate of asymptomatic COVID-19 was low, ethnic disparities were present with Hispanics being more likely to have the infection. Key Points 4.6% of pregnant women in labor and delivery tested positive for COVID-19 while being asymptomatic. Hispanic women were more likely to test positive for severe acute respiratory syndrome coronavirus 2. Pregnancy outcomes were similar between COVID-19 positive and negative women. No vertical transmission was detected.